AB0161 CLONAL HEMATOPOIESIS IS INCREASED AND NOT RELATED TO AGING IN SYSTEMIC SCLEROSIS. (13th June 2020) - Ricard, L.; Hirsch, P.; Mohty, M.; Fain, O.; Gaugler, B.; Rossignol, J.; Delhommeau, F.; Mekinian, A.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by fibrosis, microangiopathy and immune dysfunctions including dysregulation of proinflammatory cytokines. Clonal hematopoiesis of indeterminate potential (CHIP) is defined by the acquisition of somatic mutations in hematopoietic stem cells leading to detectable clones in the blood. Recent data have shown a higher risk of cardiovascular disease in patients with CHIP resulting from increased production of proinflammatory cytokines and accelerated atherosclerosis. Eventual links between CHIP and autoimmune diseases are undetermined. Objectives: The aim of our study was to evaluate the prevalence of CHIP in SSc patients and its association with clinical phenotype. Methods: Forty-one genes frequently mutated in myeloid malignancies were sequenced in peripheral blood mononuclear cells from 90 SSc patients and from 44 healthy donors. Results: A total of 15 somatic variants was detected in 13/90 SSc patients (14%) and 4 somatic variants in 4/44 (9%) HD (p=0.58). The prevalence of CHIP was significantly higher in younger SSc patients than in HD: 25% (6/24) vs 4% (1/26) (p=0.045) under 50 years and 17% (7/42) vs 3% (1/38) (p=0.065) under 60 years. The prevalence of CHIP in patients over 70 years was similar in SSc patients and healthy donors For SSc patients the most common mutations occurred in DNMT3A (7 variants). Other variants involved ATM, SF3B1, SETBP1, TET2, TP53, NF1 or CBL . The distribution of gene mutations was overall comparable in SSc patients and in previously described CHIP series (3) In most SSc patients, we identified a single CHIP mutation. Several mutations were detected in two SSc patients: SETBP1 and NF1 in one and, TET2 and ATM in the other Clonal mutations included missense (n=10), nonsense (n=3), frameshift (n=1) and a single splice site mutation. In all HD we detected a single CHIP mutation which occurred in DNMT3A, TP53 and CSF3R Variant allele frequencies (VAF) of CHIP mutations ranged from 2 to 18.6% and did not differ between genes ( DNMT3A or others). Mean age was the same in patients with DNMT3A mutations or with other mutations. However, C>T transversions, that have been associated with ageing were more frequent in DNMT3A variants than in other genes, suggesting distinct mechanisms for mutation acquisition or clonal selection No major differences in clinical and laboratory data were observed between SSc patients with or without CHIP. SSc subtypes, disease duration, different organ involvements and the prevalence of ischemic events were not associated with the presence of CHIP, except less frequent pyrosis in patients with CHIP than those without. SSc patients with CHIP had significantly more anti-RNA polymerase III antibodies than those without CHIP (p=0.045) At the time of analysis, 45 SSc patients had received a treatment for SSc which consisted in low-dose steroids, hydroxychloroquine, mycophenolate mofetil, cyclophosphamide or methotrexate. SSc patients with CHIP were significantly more exposed to cyclophosphamide (3/13 vs. 3/77) (p=0.04) (5, 6.5 and 11 gram respectively between 5 years to 8 years before the NGS sequencing analysis), but among these cyclophosphamide-exposed SSc the age was over 65 in 2/3 of them. When considering all immunosuppressive drugs (cyclophosphamide, methotrexate and mycophenolate mofetil) SSc patients with CHIP were not more exposed than those without CHIP (p=0.75) No patient developed any hematologic malignancy and no cytopenia during the median follow-up of 13 months (0-24 months). One SSc patients with CHIP developed a small lung cancer few months after NGS testing. Conclusion: Whether CHIP increases the risk to develop SSc or is a consequence of a SSc-derived modified bone marrow micro-environment remains to be explored. Acknowledgments: na Disclosure of Interests: None declared